Genetic epidemiology of multiple sclerosis. - Sadovnick, A; Dyment, D; Ebers, G (1997)
The continuing search for genetic loci which may influence multiple sclerosis susceptibility has probably been more complex and exciting than Spielman and Nathanson (4) could have imagined in 1982. Restriction fragment length polymorphisms no longer represent the "cutting edge" of technology. This entire area of research has gained incredible impetus with advances in molecular genetics and the advent of the "Human Genome Project." Readers must be cautioned that identification of a gene does not equate with a cure. Nevertheless, we are entering into a very exciting era with respect to the genetics and treatment of common complex disorders such as breast cancer, Alzheimer disease, and multiple sclerosis. Given the increasing awareness of the public about the role of genetics in the etiology of such disorders, a better understanding is needed of the legal, social, ethical, and psychologic implications of genetic research in multiple sclerosis.